2014
DOI: 10.1371/journal.pone.0106597
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Live-Attenuated Vesicular Stomatitis Virus Vector Displaying Conformationally Intact, Functional HIV-1 Envelope Trimers That Elicits Potent Cellular and Humoral Responses in Mice

Abstract: Though vaccination with live-attenuated SIV provides the greatest protection from progressive disease caused by SIV challenge in rhesus macaques, attenuated HIV presents safety concerns as a vaccine; therefore, live viral vectors carrying HIV immunogens must be considered. We have designed a replication-competent vesicular stomatitis virus (VSV) displaying immunogenic HIV-1 Env trimers and attenuating quantities of the native surface glycoprotein (G). The clade B Env immunogen is an Env-VSV G hybrid (EnvG) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 99 publications
1
25
0
Order By: Relevance
“…Six rVSV vectors expressing SIVmac239 inserts were used in this experiment. Five were based on a VSV Indiana vector in which the G gene was repositioned to the 5’ terminus of the genome [ 78 ]. By placing the G gene in the most distal gene position relative to the promoter (6 th position), its expression was modestly downregulated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six rVSV vectors expressing SIVmac239 inserts were used in this experiment. Five were based on a VSV Indiana vector in which the G gene was repositioned to the 5’ terminus of the genome [ 78 ]. By placing the G gene in the most distal gene position relative to the promoter (6 th position), its expression was modestly downregulated.…”
Section: Methodsmentioning
confidence: 99%
“…The five VSV constructs based on this vector included: 1) rVSV-EnvΔct 4 -G nj6 encoded SIV Env protein with a cytoplasmic tail that was truncated by 159 aa at its carboxyl terminus. This modification increased Env surface expression and genetic stability of rVSV-Env4-G nj6 -infected cells in vivo [ 78 , 79 ]. The envΔct 4 gene was inserted into the 4 th position relative to the 3’ end of the VSV genome.…”
Section: Methodsmentioning
confidence: 99%
“…odomain and membrane-proximal external region joined to the vesicular stomatitis virus G transmembrane and cytoplasmic domains on its surface (34). V1cycP gp120 molecule is a trimeric cyclic permutant of gp120, made by introducing new N and C termini at the V1 loop (at amino acids 144 -142) while connecting the original N and C termini with a short linker.…”
Section: Design Of Hiv-1 Outer-domain Immunogensmentioning
confidence: 99%
“…The deleted sequences included the target RT-qPCR amplicon used to detect gag in the gRNA assay, which explained reduction in signal compared to the N amplicon. This result also demonstrated that the duplex qPCR assay and gene quantity ratios could be used to effectively monitor gene insert stability in vivo, which provided valuable practical data for guiding future vector development by specifically showing that for some foreign genes alternative gene optimization approaches were needed to generate genetically stable negative-strand RNA virus vectors (Rabinovich et al, 2014).…”
Section: Discussionmentioning
confidence: 88%